2013
DOI: 10.1016/j.sdentj.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Nickel and chromium levels in the saliva of a Saudi sample treated with fixed orthodontic appliances

Abstract: Fixed orthodontic appliances resulted in a non-toxic increase in salivary levels of Ni, but no change in Cr levels. Duration of orthodontic treatment did not affect Ni and Cr levels in the saliva.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Table 2 shows the characteristics of 14 studies included in this meta-analysis. Four studies had been conducted in India [2,10,22,23], three in Iran [24,25,26], one in Norway [5], one in Turkey [13], one in Brazil [11], one in Greece [4], one in Morocco [6], one in Saudi Arabia [15], and one in Germany [1]. Two studies [1,22] reported the median (quartile) of the salivary level of ions, two studies [4,5] reported the median (range), and one study [6] reported the mean (range) values.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 shows the characteristics of 14 studies included in this meta-analysis. Four studies had been conducted in India [2,10,22,23], three in Iran [24,25,26], one in Norway [5], one in Turkey [13], one in Brazil [11], one in Greece [4], one in Morocco [6], one in Saudi Arabia [15], and one in Germany [1]. Two studies [1,22] reported the median (quartile) of the salivary level of ions, two studies [4,5] reported the median (range), and one study [6] reported the mean (range) values.…”
Section: Resultsmentioning
confidence: 99%
“…Among the six case-control studies included in this meta-analysis, two studies [15,26] showed significantly higher nickel level in patients under orthodontic treatment than controls and two studies [32,44] did not show any significant difference between the two groups, but two other studies [9,34] showed a lower level in patients compared to controls ( P > 0.05). Also, evaluation of chromium level in five studies revealed that three studies [26,34,44] reported a higher level in patients compared to controls ( P > 0.05) while two other studies [9,15] reported a lower level in patients compared to controls. Meta-analysis of two eligible case-control studies [15,26] showed a higher level of nickel, but a lower level of chromium without a significant difference between the two groups of patients and controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The release of metal ions into the body has been studied in various conditions. Nickel and chromium levels in saliva [5][6][7], in serum [8,9], and in urine [10,11] have been evaluated by previous researchers, after periods of treatment with fixed orthodontic appliances, but the results were not consistent. The nickel and chromium levels on saliva of fixed orthodontic wearers were increase [12,13] after certain period of treatment, however the levels were not significantly different after a period of 30-90 day [14].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is contrary to ours as we found no differences in salivary electrolytes with metallic and ceramic brackets. Talic et al ( 15 ) reported that installment of fixed orthodontic appliances lead to non-toxic salivary nickel level increase during the therapy, unlike salivary chromium level which remained stable. This finding is not in concordance with our results as we found decreased chromium levels and no change in salivary nickel concentration 6 month after the insertion of orthodontic appliance.…”
Section: Discussionmentioning
confidence: 99%